2015
DOI: 10.1039/c5cp01067e
|View full text |Cite
|
Sign up to set email alerts
|

Transient low-barrier hydrogen bond in the photoactive state of green fluorescent protein

Abstract: In this paper, we have analyzed the feasibility of spontaneous proton transfer in GFP at the Franck-Condon region directly after photoexcitation. Computation of a sizeable portion of the potential energy surface at the Franck-Condon region of A the structure shows the process of proton transfer to be unfavorable by 3 kcal mol(-1) in S1 if no further structural relaxation is permitted. The ground vibrational state is found to lie above the potential energy barrier of the proton transfer in both S0 and S1. Expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 54 publications
(87 reference statements)
1
18
1
Order By: Relevance
“…However, this hypothesis of causality between a photoactivated low frequency mode and the ESPT has been questioned in recent works. 26 , 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this hypothesis of causality between a photoactivated low frequency mode and the ESPT has been questioned in recent works. 26 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…A more accurate description of the kinetics would have required the computation of a larger number of excited state trajectories and the use of high level wavefunction methods, 17 , 25 , 26 , 34 36 , 39 , 40 for example by adopting precomputed and high level parameterized potentials, and also including quantum effects. 25 , 26 , 39 , 40 However, these treatments are unfeasible when including dynamical effects of the chromophore and the entire protein, with no structural restraint in the excited state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,28 Engineering chromophore variants combined with simulation analysis demonstrated that appropriate perturbations to the chromophore or its environment lead to ESPT twisting to a more energetically favorable pathway, and molecular isomerization is more favorable after excitation; all of these result in a lower energy barrier between the ground and excited states. 13,29,30 Introducing the F145Y substitution into Green2 significantly lowered the transfer energy from the ground to the excited state, even in an acidic environment ( Figure 5). Accordingly, the QY of Green after introducing F145Y increased markedly, in line with previous results showing that QY of cyan FP with substitution of H148D is much higher than with two substitutions of Y145F and H148D.…”
Section: Qy Is Elevated By a Lower Barrier Between Ground And Excitmentioning
confidence: 99%